2021
DOI: 10.1073/pnas.2004838117
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of off-target effects in CRISPR-based gene drives in the human malaria mosquito

Abstract: CRISPR-Cas9 nuclease-based gene drives have been developed toward the aim of control of the human malaria vector Anopheles gambiae. Gene drives are based on an active source of Cas9 nuclease in the germline that promotes super-Mendelian inheritance of the transgene by homology-directed repair (“homing”). Understanding whether CRISPR-induced off-target mutations are generated in Anopheles mosquitoes is an important aspect of risk assessment before any potential field release of this technology. We compared the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…These data indicated that off-target editing did not occur or occurred infrequently. Our data are comparable to the negligible off-target frequencies from Anopheles gambiae in which the impact of off-target effects on a gene drive strategy was determined 38 .
Figure 8 Off-target analysis of the w and cn sgRNAs.
…”
Section: Resultssupporting
confidence: 75%
“…These data indicated that off-target editing did not occur or occurred infrequently. Our data are comparable to the negligible off-target frequencies from Anopheles gambiae in which the impact of off-target effects on a gene drive strategy was determined 38 .
Figure 8 Off-target analysis of the w and cn sgRNAs.
…”
Section: Resultssupporting
confidence: 75%
“…Therefore, they serve as a reliable and efficient experimental tool. They have a number of specific advantages over alternatives including less specific Cre expression systems, global gene knockout and even CRISPR-Cas9, which itself is widely accepted in its current form to introduce off-target Cas9 cleavage events across species and to activate the TP53 pathway signalling ( Tsai et al, 2015 ; Enache et al, 2020 ; Garrood et al, 2021 ). To our knowledge, our study is the first one to systematically examine these effects in the liver of WT mice.…”
Section: Discussionmentioning
confidence: 99%
“…Pattanayak et al proved that the off-target efficiencywas up to 84% [61] . Recently, researchers have conducted several studies to reduce the off-target effects of CRISPR/Cas systems [62] , [63] . Several excellent reviews focusing on this topic have also been published [64] , [65] , [66] .…”
Section: Challenges Of Biosafety Materials Applied In Crispr/cas Systemsmentioning
confidence: 99%